Meta-Analysis of The Effect of Integration Stem Education in a Various Learning Models on Student Physics Learning Outcomes - Nof Putria Tenti; - Asrizal; - Murtiani; - Gusnedi (PILLAR OF PHYSICS EDUCATION, 2020)
The development of science and technology is developing rapidly in the 21st century. The development of knowledge and technology is needed to support human resources to produce quality education. At the 2013 curriculum, integrated learning is important to do to improve students' learning outcomes. One of the skills that students need was problem solving skill. However, the real conditions showed that physics learning outcomes are still low, students have low critical thinking skills, learning is still monodisciplinary, and creative thinking is still low. One solution to solve this problem is to integrate STEM education into learning. This research was conducted by analyzing the data from the article to specify the influence of STEM education integration in learning on student learning outcomes. This research is called a meta-analysis. There were 20 articles analyzed in this research, 6 articles were international and 14 articles were national. The results showed that integration of STEM education in learning has a significant effect on the level of class XI than class X of Senior High School. Then, the integration of STEM education has a significant effect on the sound wave material with an average effect size of 2.45. The integration of STEM education has a significant effect on student learning outcomes in the knowledge aspect with an average effect size of 1.83. The last, integration of STEM education provides a meaningful impact on problem-based learning with an average effect size of 2.17